ANALISIS STRATA NORMA PUISI “SEBAB DI KAU” DITINJAU DARI SEGI LAPIS DUNIA DAN LAPIS METAFISIS KARYA AMAR HAMZAH - Taufik Taufik; Susiati Susiati; Novita Sari P. Masuku (Kantor Bahasa Provinsi Maluku Utara, 2021)
Poetry can be viewed from various aspects, including the strata of norms, semiotics, the meaning of class, and so on. The purpose of this research is to describe the form of the poetry